Comparison of Treatment Outcomes among Second-Line Antiretroviral Regimens in HIV/AIDS Patient - Winda Dwi Puspitasari; Nanang Munif Yasin; Fita Rahmawati (Faculty of Pharmacy, Universitas Gadjah Mada)
Antiretroviral (ARV) therapy can increase life expectancy of people living with HIV/AIDS (PLWHA). If the therapy fails and causes severe toxicity to first-line ARV, the first-line ARV regimen is switched to the second line. Studies on the outcome of the second-line ARV therapy have not been widely conducted in Indonesia. This study aims to identify the comparison of outcomes of the second-line ARV therapy regimens in HIV/AIDS patients. The study employed retrospective cohort design. Medical record data were collected from patients treated from January 2008 until December 2017 at Dr. Kariadi Hospital of Semarang. The number of samples that met the inclusion criteria was 42 patients. The comparison between incidence of opportunistic infections and survival among the regimens was presented descriptively. The comparison of regimens based on changes in CD4 level was performed by using Kruskal-Wallis test. The switch occurred in 24 patients (57.14%) due to toxicity of the first-line ARV and in 18 patients (42.86%) due to treatment failure. Mean CD4 and viral load during the switches were 164.68 ± 204.98 cells/mm3, 154,726.14 ± 296,797.12 copies/ml respectively. After 6 months of the second-line ARV therapy, there was an increase in CD4 level (p 0.05) among the three regimens after 6 months of the second-line ARV therapy.